Magnesium Substitution in Ni‐Rich NMC Layered Cathodes for High‐Energy Lithium Ion Batteries. Issue 8 (5th January 2022) - Gomez‐Martin, Aurora; Reissig, Friederike; Frankenstein, Lars; Heidbüchel, Marcel; Winter, Martin; Placke, Tobias; Schmuch, Richard
Abstract: Ni‐rich LiNi1− x − y Mn x Co y O2 (NMC) layered oxides are promising cathode materials for high‐energy density lithium ion batteries but suffer from severe capacity fading upon cycling. Elemental substitution (= doping) with Mg has repeatedly attracted attention in NMC materials to overcome instability problems at reasonable cost, yet rational compositional tuning is needed to guarantee sufficient cycle life without compromising energy density on the material level. Herein, a series of Mg‐substituted NMC materials with 90 mol% Ni are investigated regarding key performance metrics in NMC || graphite full‐cells benchmarked against LiNi0.80 Mn0.10 Co0.10 O2 and LiNi0.90 Mn0.05 Co0.05 O2 synthetized using the same co‐precipitation route. A linear correlation between cycle life and attainable gravimetric capacities is demonstrated, which are directly influenced by the degree of Mg substitution and the amount of Li + cycled upon (de‐)lithiation processes. A Mg content <2 mol% should be considered to take notable benefit from the increase in Ni content from 80 to 90 mol% to achieve a higher energy density. The present study highlights the importance of evaluating the true implications of elemental substitution on cell performance and is expected to be an insightful guideline for the future development of NMC‐type cathode materials in particular with high Ni and low Co content. Abstract : Herein,  the impact of Mg substitution on the structural and electrochemical properties of Ni‐rich NMC‐type layered oxides is comprehensively evaluated. Increasing the Mg content in the Li interlayer linearly reduces the initial capacities and specific energies due to a limited lithium extraction ratio at a certain upper cut‐off cell voltage, but the cycle life is significantly extended.